Estimation of cytoprotective effect of bismuth tripotassium dicitrate on gastric mucosa at H. pylori eradication and long-term drug intake - A. V. Kononov; S. I. Mozgovoi; L. B. Rybkina; S. S. Bunova; A. G. Shimanskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To identify cellular «target» of bismuth tripotassium dicitrate (De-nol) therapy – DNA protection of generative zone cells of stomach mucosa (SM) from damages by oxidative burst products in neutrophilic leukocytes at continued intake of the drug for 4 wks after the ending of eradication therapy.Material and methods. Overall 53 patients after successful eradication therapy for chronic H. pyloriassociated gastritis were investigated: in 28 of them De-nol treatment was continued, 25 were included to the group of comparison. At control upper GI endoscopy biopsy samples were taken from 5 SM points according to OLGA-system protocol. In biopsy specimens presence of neutrophilic infiltration was estimated in mucosal generative zones exclusively. Borders of a generative zone were determined by the presence of myofibroblasts surrounding glandular epithelium which were identified immunohistochemically, using smooth-muscle actin as a marker. Cells with damaged DNA were revealed by immunehistochemical detection of Р53 protein.Results. No correlation between neutrophilic infiltration of SM and р53-positive cells quantity in generative zone (–0,14≤r≤0,08) was revealed in both groups. Comparison of cumulative scores of P53 label in generative zones epithelium after treatment demonstrated no significant difference between groups. Only at comparison of P53 expression level in each sampling point statistically significant differences before and after treatment (Wilcoxon W-matched-pairs ranks criterion) have been found only in group of patients who continued treatment.Conclusions. Detection of the damaged DNA in SM generative zone cells by immunehistochemical assay of P53-positive cells allows to establish significant decrease of their number in biopsies of the patients, who received the drug after cessation of eradication therapy that can be considered as a marker of protective effect for generative zone cells — cytoprotective «target» of bismuth drug.